Measurement Invariance of Psychotic-Like Symptoms as Measured With the Prodromal Questionnaire, Brief Version (PQ-B) in Adolescent and Adult Population Samples - Lång, Ulla; Mittal, Vijay Anand; Schiffman, Jason; Therman, Sebastian (Frontiers in Psychiatry, 2021)
Valid measurement of group differences in self-reported psychotic-like experiences (PLEs) requires knowing any group-specific measurement properties of the instruments. We investigated the measurement invariance of the 21-item Prodromal Questionnaire–Brief (PQ-B) questionnaire across gender, ethnic minority/majority status, and presence of depressive symptoms in two different US non-clinical undergraduate samples (N = 1103). For each item, endorsement of the experience and the associated distress were combined for analysis. A unidimensional model of the PQ-B fit the data well. Across genders, the PQ-B showed configural and metric, but not full scalar invariance; there were statistically significant differences in eight thresholds of six items, most being higher endorsement thresholds for self-identified females. Partial scalar invariance was also found for ethnic status, with five thresholds of three items being higher for the minority participants. For depressive symptomatology, defined as the top quintile by the Beck Depression Inventory–II, partial scalar invariance required dropping one item, after which there were statistically significant differences only in two response thresholds. Overall, a wide range of PLE questionnaire items were found to be robust to gender and ethnicity effects, strengthening confidence in found group differences in PLEs. Although full scalar invariance could not be ascertained for any of the group comparisons, the few found scalar differences across groups were small, with minimal impact on group PLE estimates. However, since PLE are easily conceptually entangled with depression symptoms, similar items should be considered for exclusion if separable constructs are the target of investigation.